“Young people are calling for more action on what they say is a climate emergency”: English Learner’s Dictionaries and the Global Environmental Issue: English - Pettini, Silvia (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
This paper aims to investigate the representation of “the defining issue of our time” (Guterres, 2018), that is, the global environmental crisis, in online English learner’s dictionaries, in light of the link between these pedagogical tools, directed at a target audience of young foreign language users (Wirag, 2021, p. 46), and the youth’s increasing concern over the climate emergency (Buchholz, 2022; Cordis, 2023; Harrabin, 2021). For this purpose, this study explores the online editions of three major British dictionaries for learners, namely, the Cambridge Advanced Learner’s Dictionary, the Collins-Cobuild Advanced Learner’s Dictionary, and the Oxford Advanced Learner’s Dictionary. These resources have been selected because their lexicographers simultaneously converged on this semantic field to identify the Words of the Year 2019, based on the increasing sociocultural relevance of the ecological crisis in spoken and written communication. Preliminary findings show many differences in the treatment of environmental terms, the quantity and quality of lexicographic data significantly vary across the three reference works, and the divergences affect the ways in which dictionaries reflect the influence of climate change on language.
Keywords: climate change; climate emergency; environment; online English lexicography; online learner’s dictionaries; Word of the Year